A Factor Analysis of Organizational Citizenship Behavior of Professional Nurse, Private Hospitals - คงเฟื่อง ปวริศา; ประจุศิลป กัญญดา (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this study was to investigate the component of organizational citizenship behavior of professional nurses, private hospitals Data were collected from the sample consisting of 364 staff nurses who had worked for at least one year experience from 3 private hospitals which accredited by joint commission international. Participants were recruited by multi-stage sampling. The research instrument was an organizational citizenship behavior of professional nurse questionnaire. The instrument was tested for content validity by five experts and cronbach’s alpha coefficient was 0.96. The data were analyzed using principle component extraction and orthogonal with varimax method. The findings were as follows: Four significant components of organizational citizenship behavior of professional nurse, private hospital were identified. There were 32 items that accounted for 67.20% which were identified respectively 1. Civic virtue and Self-development by 10 items accounted for 19.85% 2. Conscientiousness by 8 items accounted for 18.52% 3. Courtesy and Sportsmanship by 8 items accounted for 15.09% 4. Altruism by 6 items accounted for 13.74%